Textuelle Formationen von Erinnerung und Gedächtnis: Linguistische Studien zum Erzählen in Uwe Johnsons »Jahrestagen« - Attig, Matthias (Sprache und Wissen, 2015)
Uwe Johnson’s novel Anniversaries weaves poetic sequences and realities into an artfully composed montage to represent a process of remembrance that is at once fragile and complex. This study combines linguistic and literary approaches to explore the unique structure of this poetics of memory – the reciprocal referentiality of memory and what is remembered – in each of its singular facets.